Skeptic’s Comment: What Questions ‘Academic Writing’ Does Not Answer - Alevtina S. Robotova (Высшее образование в России, 2018)
The paper provides information to support its title (“Skeptic’s comment…”). The author shares his attitudes towards a new research area of academic writing (AW) and a system of teaching AW. The paper is presented in a form of a dialog between the author and the advocates of AW. In the author’s opinion, these advocates do not answer a number of questions to be asked for including their ideas into the scope of pedagogical knowledge. While admitting the value of analyzing foreign publications on AW, interpreting them and creating a teaching and learning system tailored for our national practice, the author states that the arguments to recognize AW as an independent academic discipline or a new research area are not sufficient. The author supports this idea by a series of speculations expanded in the paper sections to follow. They include doubts about the completeness of methodological arguments (considering the contemporary state of matter in epistemology, attitude towards new type rationality, unique features of cognition in science and humanities, rationale for the relevance of social constructivism for AW, and etc.), and about the insufficient attention towards the contemporary pedagogical methodology. The status of AW is discussed as if sidestepping the national achievements in investigating the language, speech, text (academic), discourse, linguistic and rhetoric conventions, and etc. The skepticism regarding the AW system can also be explained by the fact that the author does not agree with a number of statements denying the figural and publicistic images in an academic style, personal characteristics, opinions, emotional experiences and beliefs; negating the talent, literature expertise and imitation as assistants for academic writing; inferring the impossibility of learning academic writing independently. The author is confused by the insufficient attention towards the investigations on eloquence carried out in the 1980s in our native country (e.g. by S.S. Averintsev, A.K. Avelichev, and etc.); it is clear that the expertise in foreign research does not negate the knowledge about the research in our native country. Through critically analyzing the components of the AW system, the author concludes that AW is to be considered as one of possible technological solutions for the problem of creating a scholarly proper academic text.